E-173 Peri-infarct acid/base and electrolyte alterations in acute large vessel occlusion stroke. (22nd July 2018) - Fraser, J; Martha, S; Collier, L; Davis, S; Abdulnasser, A; Grupke, S; Pennypacker, K
Abstract : Introduction: In the setting of mechanical thrombectomy for emergent large vessel occlusion (ELVO), we have for the first time developed a protocol to collect and evaluate blood immediately distal and proximal from the removed intracranial thrombus. These samples provide a unique resource in evaluating acute changes in acid/base and electrolyte concentrations at the time of ischemic stroke. The purpose of this study is to compare acid/base and electrolyte differences obtained proximal and distal to the occluded intracranial thrombus in acute ischemic stroke patients. Methods: We developed the BACTRAC protocol: an IRB-approved tissue banking strategy for ELVO (clinicaltrials.gov NCT03153683 ). We compared arterial blood gases (ABG) of blood distal versus proximal to the thrombus during thrombectomy. Comparisons were evaluated by Paired Samples T-Tests (p<0.05). Results: We analyzed the first 24 subjects (age=65±0.54, 11 males) in the BACTRAC registry. Preliminary results demonstrate that, while pH is nonsignificant, distal blood in relation to proximal blood showed significantly lower oxygen (p=0.010), carbon dioxide (p=0.001), bicarbonate (p=0.002), ionized calcium (p=0.001), and potassium (p=0.001). Sodium concentration was significantly higher (p=0.002) in distal blood. These results suggest alterations occurring intravascularly during ischemia. Conclusion: These findings provide a novel insight into the pathology of large vessel stroke in humans, particularly in regard to identifying acute changes in acid/base balance and electrolyte concentrations that occur during stroke. Disclosures: J. Fraser: None. S. Martha: None. L. Collier: None. S. Davis: None. A. Abdulnasser: None. S. Grupke: None. K. Pennypacker: None.